Melt inclusions in quartz and topaz of the topaz granite from Eurajoki, Finland - Haapala,I.; Thomas,R. (Journal of the Czech Geological Society, 2000)
Crystallized melt inclusions occur in quartz and topaz of the topaz granite (Vakkara granite) of the 1.57 Ga Eurajoki rapakivi granite stock. Large silicate melt inclusions in quartz were fused to homogenization and the glass was analyzed by electron microprobe. The granitic melt inclusions are peraluminous and enriched in fluorine and tin (7.3 - 0.4 wt % F, 0.03 wt % SnO2), enabling magmatic crystallization of topaz. Together with recent corresponding observations from other highly evolved granites, the study demonstrates the important role of magmatic processes in formation of tin granites and other F-rich granites.
Keywords: Topaz granite; rapakivi granite; melt inclusions; cassiterite; magmatic evolution